THE CATLIN MULTITYPE OF SUMS OF SQUARES DOMAINS - AIDOO, NICHOLAS (Trinity College Dublin. School of Mathematics. Discipline of Pure & Applied Mathematics, 2021)
Given a sum of squares domain of finite D'
APPROVED
Keywords: multitype; ideal